Smartovation Yuza with long dependable wires / Mahamad Hamid ... [et al.] - Hamid, Mahamad; Zolkifli, Muhammad Aliff Azfar; Jehan, Muhammad Lutfi; Mazri, Anuarmuhammad Aiman Haziq; Osman, Muhammad Irfan (Universiti Teknologi MARA, Kedah, 2019)
Smartovation Yuza with Long Dependable Wires or known as portable socket which can be used in any building such as at home, workshop and et cetera. This socket applies the concept of physics which is the spring elasticity to rotate the rod to its original position when the force applied to its deverted. Elasticity is the ability of a material to return to its original shape after being stretched or compressed. When an elastic material is stretched or compressed, it exerts elastic force. This force increases the more the material is stretched or compressed.This elasticity is caused by the attraction or repulsion of the object. From the analysis,we get to know that this project has a big effects from the elasticity of the spring. So the more the elasticity of the spring, the easier to pull out the socket from it’s place. The extension of the spring also increases when the force is increases as long as it is not exceeding the elasticity limits. Last but not least, this project can also leads to people’s interest especially in engineering field. For the conclusion, this project gave a big impact to increase the technology in our world.